Olfactory rule learning-induced enhancement in intrinsic neuronal excitability is maintained by shutdown of the cholinergic M-current - Awasthi, Richa; Chandra, Naveen; Barkai, Edi (Frontiers in Cellular Neuroscience, 2022)
Training rats in a particularly difficult olfactory discrimination task initiates a period of accelerated learning, manifested as a dramatic increase in the rats' capacity to discriminate between new pairs odors once they have learned the first discrimination task, implying that rule learning has taken place. At the cellular biophysical level, rule learning in maintained by reduction in the conductance of the slow calcium-dependent potassium current (sIAHP) simultaneously in most piriform cortex layer II pyramidal neurons. Such sIAHP reduction is expressed in attenuation of the post-burst after-hyperpolarization (AHP) potential, and thus in enhanced repetitive action potential firing. Previous studies show that a causal relationship exist between long-lasting post-burst AHP reduction and rule learning. A specific channel through which the sIAHP current flows has not been identified, and possibly does not exist. The sIAHP in pyramidal cells is critically dependent on membrane phosphatidylinositol 4,5-bisphosphate [PtdIns(4,5)P(2)]. PtdIns(4,5)P(2) regulates the calcium sensitivity of sIAHP by acting downstream from the rise in intracellular calcium. These findings led to the interesting hypothesis that PtdIns(4,5)P(2) activates a variety of potassium channels. Thus, the sIAHP current would not represent a unitary ionic current but the embodiment of a generalized potassium channel gating mechanism. Here we first show, using current clamp recordings, that the post burst AHP in piriform cortex pyramidal neurons is mediated also by currents other the known calcium-dependent potassium currents, which are also affected by learning. We also show, using whole cell patch clamp recordings, that learning-induced reduction in the post burst AHP results from long-term reduction of the PtdIns(4,5)P(2)- mediated activation of the M muscarinic acetylcholine receptor.